Southern Ocean sea ice and frontal changes during the Late Quaternary and their linkages to Asian summer monsoon. (1st June 2019) - Nair, Abhilash; Mohan, Rahul; Crosta, Xavier; Manoj, M.C.; Thamban, Meloth; Marieu, Vincent
Abstract: The present study documents the interactions between Southern Hemisphere high-latitude (Antarctica & Southern Ocean), southern Indian Ocean subtropics (Agulhas leakage) and Asian summer monsoon. The study uses SST and sea-ice reconstructions along with diatom absolute abundances and diatom biometry from two sediment cores located at the Subantarctic Front (SAF) and Antarctic Polar Front (APF) in the southwest Indian sector of the Southern Ocean. Sea-ice records suggest the presence of the mean winter sea ice limit at around the modern APF location during MIS 2 and MIS 4 and episodic and unconsolidated winter sea ice far north as ∼43°S during LGM, when the SSTs were lowest. Higher diatom productivity and larger mean sizes of F. kerguelensis and T. lentiginosa recorded at the northern core site during the glacial stages suggest a northward shift of the APF. A decrease in diatom productivity and sizes at the southern core site highlights stratified Permanent Open Ocean Zone (POOZ) surface waters in response to longer sea-ice presence during the glacial stages. The comparative study between the records of Southern Hemisphere high-latitude and Asian summer monsoon climate variability revealed that the Asian summer monsoon variability could have been more likely forced by low latitude insolation gradient changes and supported by Antarctic climate changes via meridional shifts of the fronts and sea ice. The past changes in the intensity of Asian summer monsoon along with the Southern Ocean frontal variation might have influenced the Southern Indian Ocean surface circulation by changing the Agulhas leakage intensity. Highlights: Diatom transfer function documents glacial mean winter sea-ice limit located at around the modern Antarctic Polar Front. Diatom biometry places the glacial APF at around 43°S. Southern Ocean modulated Asian summer monsoon via its impact on the Agulhas leakage and southern Indian Ocean subtropical high.